Contention minimized bypassing in SMART NoC - Chen, Peng (2020)
SMART, a recently proposed dynamically reconfigurable NoC, enables single-cycle long-distance communication by building single-bypass paths. However, such a single-cycle single-bypass path will be broken when contention occurs. Thus, lower-priority packets will be buffered at intermediate routers with blocking latency from higher-priority packets, and extra router-stage latency to rebuild remaining path, reducing the bypassing benefits that SMART offers. In this paper, we for the first time propose an effective routing strategy to achieve nearly contention-free bypassing in SMART NoC. Specifically, we identify two different routes for communication pairs: direct route, with which data can reach the destination in a single bypass; and indirect route, with which data can reach the destination in two bypasses via an intermediate router. If a direct route is not found, we would alternatively resort to an indirect route in advance to eliminate the blocking latency, at the cost of only one router-stage latency. Compared with the current routing, our new approach can effectively isolate conflicting communication pairs, greatly balance the traffic loads and fully utilize bypass paths. Experiments show that our approach makes 22.6% performance improvement on average in terms of communication latency.